Job the Unfinalizable : A Bakhtinian Reading of Job 1-11. - Hyun, Seong Whan Timothy. (Biblical Interpretation Series, 2013)
In Job the Unfinalizable , Seong Whan Timothy Hyun reads Job 1-11 through the lens of Bakhtin's dialogism and chronotope to hear each different voice as a unique and equally weighted voice. The distinctive voices in the prologue and dialogue, Hyun argues, depict Job as the unfinalizable by working together rather than quarrelling each other. As pieces of a puzzle come together to make the whole picture, all voices in Job 1-11 though each with its own unique ideology come together to complete the picture of Job. This picture of Job offers readers a different way to read the book of Job: to find better questions rather than answers.